Diagnostic Imaging Features of Various Affections of Udder and Teat in Goats - Paray, Aaquib Hussain; Parmar, Jignesh J; Mecvan, Arnold R; Dabhi, Prashant B; Parikh, Pinesh V (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was carried out on 30 goats with various udder and teat affections. The diagnostic imaging modalities comprised of plain, positive, negative and double contrast radiographic, and ultrasonography of healthy as well as affected udder and teat. Radiography and ultrasonography were effective tools for diagnosis of various affections of teat and udder of goat. Double contrast technique among the plain, negative and positive contrast radiography, and water-bath technique among ultrasonography were most suitable for diagnosis of various teat affections in goats.
Keywords: Diagnostic Imaging; Goat; Radiography; Teat; Udder; Ultrasonography